The abolition of taxes on knowledge - Oats, L.; Sadler, Pauline (Hart Publishing, 2007)
When first introduced in 1712, and throughout the eighteenth century, thestamp duty on newspapers was primarily intended as a revenue raiser with censorshipas a subsidiary, but not Wlintended, by-product. In the nineteenth centurythe stamp duty became known more justifiably as a 'tax on knowledge'and it was increasingly criticised as being an overt form of statutory censorship.Efforts to have the tax repealed resulted in a compromise in 1836, witha significant reduction in the duty from 4d to 1d. The stamp duty was eventuallyrepealed in 1855, largely as a result of the activities of 'The NewspaperStamp Abolition Committee' and the findings of the 'Select Committee onNewspaper Stamps'. The purpose of the paper is to give a brief account of the history of the stamp duty up to 1836 and then to examine the events between 1836 and 1855.